EMPLOYEE ENGAGEMENT- “TRENDS AND DYNAMICS OVER PAST TWO DECADES – CHRONOLOGICAL LITERATURE REVIEW” - Mehta, Mita Nishant; Devi, Vaishnavi; Hajela, Tanu; Chandani, Arti (International Journal of Psychosocial Rehabilitation, 2020)
Employee engagement is continuously evolving especially over past two decades. It is only engaged employee who will go extra mile to achieve organizational goal. This review paper provides an in-depth knowledge on how employee engagement trends have evolved over past two decades (1998-2018). Employee engagement is the degree of commitment an employee has towards his or her organization. It will also help to learn how employee engagement is used as a tool to retain employees. With the help of this review paper, further the failures in engaging employees can be understood and accordingly Human Resource Management can come up with new strategies. This study will be useful to researchers, scholars and human resource strategist to build further set of action.